Mutations in the ABCA4 (ABCR) gene are the major cause of autosomal recessive cone-rod dystrophy - Maugeri, Alessandra; Klevering, B. Jeroen; Rohrschneider, Klaus; Blankenagel, Anita; Brunner, Han G.; Deutman, August F.; Hoyng, Carel B.; Cremers, Frans P. M. (The American journal of human genetics, 2000)
The photoreceptor cell-specific ATP-binding cassette transporter gene (ABCA4; previously denoted “ABCR”) is mutated in most patients with autosomal recessive (AR) Stargardt disease (STGD1) or fundus flavimaculatus (FFM). In addition, a few cases with AR retinitis pigmentosa (RP) and AR cone-rod dystrophy (CRD) have been found to have ABCA4 mutations. To evaluate the importance of the ABCA4 gene as a cause of AR CRD, we selected 5 patients with AR CRD and 15 patients with isolated CRD, all from Germany and The Netherlands . Single-strand conformation-polymorphism analysis and sequencing revealed 19 ABCA4 mutations in 13 (65%) of 20 patients. In six patients, mutations were identified in both ABCA4 alleles; in seven patients, mutations were detected in one allele. One complex ABCA4 allele (L541P;A1038V) was found exclusively in German patients with CRD; one patient carried this complex allele homozygously, and five others were compound heterozygous. These findings suggest that mutations in the ABCA4 gene are the major cause of AR CRD. A primary role of the ABCA4 gene in STGD1/FFM and AR CRD, together with the gene's involvement in an as-yet-unknown proportion of cases with AR RP, strengthens the idea that mutations in the ABCA4 gene could be the most frequent cause of inherited retinal dystrophy in humans.
Gesehen am 03.03.2021